2021
DOI: 10.1039/d0py01696a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling properties of thermogels by tuning critical solution behaviour of ternary copolymers

Abstract: Thermogelling tri-block terpolymers were made from a bifunctional PEG RAFT agent. The critical solution behavior was tunable by alteration of the terpolymer composition, enabling modulation of gelation temperatures and hydrogel viscoelasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Furthermore, the LCST value of PNIPAM can be tuned by copolymerizing with other hydrophilic/hydrophobic monomers together with PNIPAM. Adding more hydrophilic monomers such as hydroxyl ethylacrylamide (HEAm) could make the LCST increase to 50 °C [ 39 ], while hydrophobic monomers such as tertbutyl acrylamide (TBAM), N-tert-butylacrylamide (NT), or butylacrylate (BA) could lower the LCST and lead to a stiffer gel [ 40 , 41 ]. Nonuniform shrinkage caused by a specific spatial arrangement of PNIPAM-based polymers with different LCST can lead to macroscopic bending, folding, twisting, and other shape transformations of the hydrogel at different temperatures, with potential use as a smart soft actuator [ 42 ].…”
Section: Thermogelling Mechanism/thermogelling Propertiesmentioning
confidence: 99%
“…Furthermore, the LCST value of PNIPAM can be tuned by copolymerizing with other hydrophilic/hydrophobic monomers together with PNIPAM. Adding more hydrophilic monomers such as hydroxyl ethylacrylamide (HEAm) could make the LCST increase to 50 °C [ 39 ], while hydrophobic monomers such as tertbutyl acrylamide (TBAM), N-tert-butylacrylamide (NT), or butylacrylate (BA) could lower the LCST and lead to a stiffer gel [ 40 , 41 ]. Nonuniform shrinkage caused by a specific spatial arrangement of PNIPAM-based polymers with different LCST can lead to macroscopic bending, folding, twisting, and other shape transformations of the hydrogel at different temperatures, with potential use as a smart soft actuator [ 42 ].…”
Section: Thermogelling Mechanism/thermogelling Propertiesmentioning
confidence: 99%
“…Figure 4 exhibited chitosan nanoparticles' rheological behavior that showed the decrease in complex viscosity, storage, and loss modulus by increasing temperature, while it demonstrated an increase in complex viscosity, storage modulus, and loss modulus for magnetic semi IPN nanogels. MTRSI-NGs curve demonstrates that when temperature rises to higher than LCST, the value of viscosity and modulus curve rises (Huang et al 2017;Smith et al 2021). As shown in Figs.…”
Section: Lcst Analysis Of Magnetic Nanogelsmentioning
confidence: 74%
“…Magnetic nanocarriers are injected intravenously. The mechanistic action of MTRSI-NGs in the body occurs by three following successions: first, magnetically conducting MTRSI-NGs to targeted tissue, second, the magnet leads to the increasing temperature of Fe 3 O 4 and then heat transfer to thermoresponsive nanogels to LCST until to protein release, third wipe out body from MTRSI-NGs (He et al 2013;Smith et al 2021;Uhrich et al 1999).Cytotoxicity of PNVCL was investigated by Han et al The results showed that PNVCL did not show toxicity with short-term cell exposure. PNVCL withstand increases in temperature, while others change from twophase to single-phase by increasing temperature (Dinari et al 2021;Fernández-Quiroz et al 2015;Siirilä et al 2019;Vihola et al 2005).Temperature responsive polymers present an excellent hydrophobic-hydrophilic balance in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…2 . In contrast, the addition of N-tert-butylacrylamide (NT), tertbutyl acrylamide (TBAM), or butylacrylate (BA) hydrophobic monomers to PNIPAAM could lower its LCST and produce a stiffer hydrogel [ 109 , 110 ]. Moreover, the affinity of dried hydrogels to water drastically changes to minor alterations in the temperature.…”
Section: Smart/stimuli-responsive Hydrogelsmentioning
confidence: 99%